Assessing the Impact of Physical Activity on Life Satisfaction among Lawyers - Shah, Syed Umair Ali; Ali, Asif; Munawar, Natasha (Annals of Human and Social Sciences, 2024)
In current modern days, lack of life satisfaction merge as major issue among various professionals including lawyers. Therefore, to assess the impact of physical activity on life satisfaction among lawyers was the primary objective of the study. The study consisted of 230 participants out of which 19 were female lawyers and 211 were male lawyers. These lawyers ranged from 25 years to 65 years (M=38.19, SD=10.08) in age. The nature of this research was quantitative cross-sectional. Participants level of PA and life satisfaction were measured using IPAQ and SWLS. The findings demonstrated a notably beneficial link between physical exercise and life satisfaction among lawyers. The findings suggested that life satisfaction may be improved by raising level of PA among lawyers. Furthermore, results also indicated that age and gender did not play any significant role. Hence, legal organizations and law firms might consider implementing wellness programs to improve LS among lawyers.